2006
DOI: 10.1117/12.653027
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of alveolar bone resorption by image processing of 3-D dental CT images

Abstract: We have developed a novel system that provides total support for assessment of alveolar bone resorption, caused by periodontitis, based on three-dimensional (3-D) dental CT images. In spite of the difficulty in perceiving the complex 3-D shape of resorption, dentists assessing resorption location and severity have been relying on two-dimensional radiography and probing, which merely provides one-dimensional information (depth) about resorption shape. However, there has been little work on assisting assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Accordingly, it was found that CBCT is quite beneficial and accurate in the diagnosis of infra-bony defects and furcation involvement. [80] Walter et al 2009 [86] Pajnigara et al 2016 [87] Grimrad et al2009 [92] Walter et al 2010 [77] Gupta V et al 2014 [90] De Faria et al2012 [71] Gupta SJ et al 2014 [90] Fiejo et al 2012 [72] Khosropana et al2015 [91] Walter et al 2012 [82] Bhavsar et al [93] Raichur et al 2012 [84] Pajnigara et al 2017 [94] Marinescu et al 2013 [79] Dutra et al 2017 [89] Qiao et al 2013 [75] Nemoto et al 2018 [95] Haghgoo et al2014 [83] Banodkar et al 2015 [68] Cimbaljevic et al 2015 [69] Darby et al 2015 [70] Li F et al 2015 [74] Guo et al 2016 [73] Zhu et al 2016 [78] Suphanantachat et al 2017 [76] Padmanabhan et al 2017 [81] Zhang et al 2018 [85] Charlotte, NC, USA) operating at 70 kVp, 7 mA , and an exposure time corresponding to the exposed area, Clinical measurements Good Quality Not clear N/A Not applicable Table 4. CASP checklist for critical appraisal of randomized clinical trials studies…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it was found that CBCT is quite beneficial and accurate in the diagnosis of infra-bony defects and furcation involvement. [80] Walter et al 2009 [86] Pajnigara et al 2016 [87] Grimrad et al2009 [92] Walter et al 2010 [77] Gupta V et al 2014 [90] De Faria et al2012 [71] Gupta SJ et al 2014 [90] Fiejo et al 2012 [72] Khosropana et al2015 [91] Walter et al 2012 [82] Bhavsar et al [93] Raichur et al 2012 [84] Pajnigara et al 2017 [94] Marinescu et al 2013 [79] Dutra et al 2017 [89] Qiao et al 2013 [75] Nemoto et al 2018 [95] Haghgoo et al2014 [83] Banodkar et al 2015 [68] Cimbaljevic et al 2015 [69] Darby et al 2015 [70] Li F et al 2015 [74] Guo et al 2016 [73] Zhu et al 2016 [78] Suphanantachat et al 2017 [76] Padmanabhan et al 2017 [81] Zhang et al 2018 [85] Charlotte, NC, USA) operating at 70 kVp, 7 mA , and an exposure time corresponding to the exposed area, Clinical measurements Good Quality Not clear N/A Not applicable Table 4. CASP checklist for critical appraisal of randomized clinical trials studies…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed eighteen studies [65,69,71,74,76,81,84,[86][87][88][89][90][91][92][93][94][95][96] on diagnostic accuracy. The QUADAS-2 assessment tool was used for quality assessment [34].…”
Section: Diagnostic Accuracy Studiesmentioning
confidence: 99%
“…The results revealed eighteen studies [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] on diagnostic accuracy. The QUADAS-2 assessment tool was used for quality assessment [38].…”
Section: Diagnostic Accuracy Studiesmentioning
confidence: 99%